Enhancing the recombinant protein productivity of Yarrowia lipolytica using in situ fibrous bed bioreactor. (November 2021) - Mou, Jin-Hua; Tahar, Imen Ben; Wang, Zhen-Yao; Ong, Khai Lun; Li, Chong; Qin, Zi-Hao; Wang, Xiang; Lin, Carol Sze Ki; Fickers, Patrick
Graphical abstract: Highlights: Strain RIY438 was constructed for increased capability to grow on a solid support. In situ fibrous bed bioreactor ( is FBB) was assessed for CalB lipase production. The maximum lipase titer (28957 ± 1005 U/mL) was achieved in is FBB culture. The lipase productivity was 1.4-fold higher in is FBB than free cell batch culture. Abstract: In this study, the ability of Yarrowia lipolytica to produce the recombinant lipase CalB from Candida antarctica, used as a model protein has been compared across different bioreactor processes using glycerol, a byproduct from the biodiesel industry as the main carbon source. Batch, pulsed fed-batch (PFB), and continuous fed-batch (CFB) strategies were first compared using classical stirred tank (STR) bioreactors in terms of biomass production, carbon source uptake, and lipase production. Additionally, an in situ fibrous bed bioreactor ( is FBB) was developed using sugarcane bagasse as a cell immobilization support. The maximum lipase titer achieved using the is FBB culture mode was 38%, 33%, and 49% higher than those obtained using the batch, PFB, and CFB cultures, respectively. The lipase productivity in is FBB mode (142 U/mL/h) was 1.4-fold higher than that obtained using batch free cell cultures. These results highlight that is FBB is an efficient technology for the production of recombinant enzymes.